MEK452 - Materials Sciences & Technology / College of Engineering - UiTM, College Of Engineering (Universiti Teknologi MARA (UiTM), 2023)
This course introduces several advanced concepts and topics in the rapidly evolving field of material science, covering some fundamentals, which are necessary for the understanding of materials properties for their appropriate applications. Students are expected to develop comprehension of the subject and to gain scientific understanding regarding the choice and manipulation of materials for desired engineering technology applications. The major families of materials such as metals, ceramics, polymers, and composite are discussed for their structures, properties, and applications.